Perancangan Sistem pencatatan progres harian proyek berbasis web di estungkara digital - Moh. Noval Prayoga; Achmad Baijuri (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This research aims to design a Web-Based Daily Project Progress Recording System at Estungkara Digital Malang using the Object-Oriented Analysis and Design (OOAD) approach. The type of research conducted is applied research, focusing on system requirements analysis and design without proceeding to the implementation stage. Data were collected through observation, interviews, and literature review to obtain a clear understanding of the ongoing project progress recording process and the challenges encountered. System analysis was carried out using Unified Modeling Language (UML) modeling tools, including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. In addition, database design was developed using the Conceptual Data Model (CDM) and Physical Data Model (PDM). The result of this research is a system blueprint that can serve as a reference for further application development. The designed system is expected to provide flexibility in data management, simplify monitoring processes, enhance reporting transparency, and support project management effectiveness at Estungkara Digital Malang.